2019
DOI: 10.7759/cureus.6346
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Of Pre-operative Oral Medication of Ibuprofen and Ketorolac on Anesthetic Efficacy of Inferior Alveolar Nerve Block with Irreversible Pulpitis: Randomized Controlled Trial

Abstract: Background and objectives Pain is the primary reason that dental patients seek endodontic therapy. The inferior alveolar nerve block (IANB) is the most frequently used mandibular injection technique for achieving local anesthesia for endodontic treatment. However, the IANB does not always result in successful pulpal anesthesia. Therefore, the purpose of this study was to determine the effects of preoperative administration of both ibuprofen and ketorolac on the efficacy of the IANB in patients with irreversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It is extremely important that all complications and side effects of any medications, techniques and interventions should be reported in clinical trials. One of the shortcomings of previously published investigations was not reporting complications following the use of anaesthetic solutions, techniques and premedication (Aggarwal et al, 2018b; Gupta et al, 2019; Kaladi et al, 2019). Future studies should more focus on these subjects.…”
Section: Post‐injection Complications and Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is extremely important that all complications and side effects of any medications, techniques and interventions should be reported in clinical trials. One of the shortcomings of previously published investigations was not reporting complications following the use of anaesthetic solutions, techniques and premedication (Aggarwal et al, 2018b; Gupta et al, 2019; Kaladi et al, 2019). Future studies should more focus on these subjects.…”
Section: Post‐injection Complications and Side Effectsmentioning
confidence: 99%
“…However, the recommendations from previous systematic reviews and meta‐analyses might change by including the results of new randomized clinical trials in a new systematic review and meta‐analysis. For instance, despite no significant effect of ketorolac in the systematic review and meta‐analysis conducted by Li et al (2012), three studies that have subsequently been published have confirmed the effect of this medication on anaesthesia success rates for mandibular molars with irreversible pulpitis (Akhlaghi et al, 2016; Kaladi et al, 2019; Yadav et al, 2015).…”
Section: Premedicationmentioning
confidence: 99%
“…Thus, the samples based on alginate (1, 2, 3) had the higher moisture content but the lower tensile than the sample based on xanthan gum (4). Adding of Carbopol 971P NF in the compositions (2,3,5) had different impact on properties of this dosage form -it increased tensile and mucoadhesion for the samples based on xanthan gum and decreased adhesion property and disintegration time for the sample based on alginate. For the alginate Manucol LKX the adding of 0.05 % Carbopol 971P NF in the composition contributed to homogeneously distribution of the substance in the thin film and also made it elasticity.…”
Section: Resultsmentioning
confidence: 93%
“…Among all these drugs for using in dentistry non-steroidal antiinflammatory drugs play an important role. Pain is the major symptom faced by patients in the process of endodontic treatment in extraction of teeth or part of the gum, after dental implant insertion etc [3][4][5]. Ketorolac is used successfully in dentistry because of strong analgesic effect comparable with narcotic analgesics, but unlike them, ketorolac does not affect at opiate receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation